The correspondence on architecture between Rubens and Huygens (1635-'40) (Bulletin KNOB, 1997)
Constantijn Huygens, the secretary of the Prince of Orange, kept up a correspondence with P.P. Rubens in the years 1635-'40. One of their main themes was architecture, in connection with the building of Huygens' own house in The Hague in the years 1634-'37 (ill. 3-6). So far, three of Huygens' letters to Rubens are known. Rubens's replies seem to have been lost.This article focuses on Huygens' draft for a fourth letter to Rubens, dating from 1640, in which he tried to refute a number of critical remarks apparently made by Rubens in a previous letter, concerning the design of Huygens House (Appendix IV). Eventually, because of Rubens' death in 1640, this letter was never written.It is obvious that Rubens thought Huygens House too simple, compared to the monumental architecture developed in Antwerp two decades before. He suggested instead of the simple Doric gate to the street to build a large arch with heavy key stones on top, possibly having the arch of the courtyard of his own house in Antwerp in mind (see ill. 2). Moreover, Rubens had a strong preference for a clustering of pilasters and wrings in the entablature of the facade, as he knew these, for instance, from the Antwerp Jesuit Church (see ill. 1). Instead of too much simplicity (la troppo simplicità) Rubens was of the opinion that such a town palace required greater dignity. According to him in the architecture of the facade this could be achieved by applying more relief and plasticity (maggior dignità e rilievo à tutta la facciata). Huygens, on the contrary, emphasized that he deliberately avoided too large a gesture (un effetto di troppo violenza) and that to him simplicity was beautiful enough in itself, provided that here too, the rules of the art would be followed (servitu delle regole antiche). So far, both parties answer the familiar image which historiography has rendered of them, Rubens as the baroque, exuberant mind and Huygens as the puritan guardian of the classical heritage.However, in this correspondence both of them also express different views, seemingly in contradiction with the positions defined above. It is Rubens who keeps harping on the need to follow the rules and proportions of Vitruvius very precisely. Remarkably enough, it is Huygens who in his counter-argument puts forward that the rules need not be observed so precisely and that they might as well be adapted to the circumstances (un poco ubedire l'arte al sito), as long as this is not experienced as disturbing (senza incommodita dell'occhio). Thus the theory of Vitruvius appears to have been used as the Standard of architecture in Antwerp in 1640, too. In the light of the tradition of the Vitruvian study, which at that time had already been practiced for one century in this city, this is not really surprising. After Coecke van Aelst, Cornelis Floris and Vredeman de Vries, to mention the major propagandists from the 16th century, this tradition of classicism continued to exist in the 17th century, too, among architects such as Cobergher and Francart and among commissioners such as Aguilon.All this provides sufficient reason to look for the common reception of the Italian Renaissance and the Vitruvian tradition in the study of 17th century-architecture in both the Netherlands, without being diverted by the striking difference in external appearance of the architecture in both provinces in that period.